Discussing the Effect of Students' Crisis Awareness on Emotion During the COVID-19 Pandemic From the Perspective of Trust - Yang, Cheng; Miao, Yinghua (Frontiers in Psychology, 2022)
The effects of crises are changeable, among individuals, society, and nation. Crisis management of the government presents great differences compared to the non-government organizations, mainly in terms of “publicity”, since it involves bureaucracy to meet the accountability concerns of people. The purpose of this study aims to discuss the relationship among students’ crisis awareness, trust, and emotion under major public health emergency. The study adopted a questionnaire survey method. 500 copies of questionnaires were distributed to the college students in Jiangxi. A total of 437 valid copies were retrieved, with a retrieval rate of 87%. Structural equation model (SEM) was utilized to conduct the statistical analyses. The research results were summarized as below. 1. People might easily fall into the negative emotion at epidemic spread stage. 2. The public with good trust relationship consider less responsibility of schools for critical incidents and helpful for crisis communication. 3. Decreasing the negative emotion in public, after the occurrence of critical incidents, may effectively reduce the harm of critical incidents for the organization. Avoiding a decrease of students’ trust and enhancing anger, protecting the organizational reputation of schools, receiving good communication effect, and reducing the impact of crisis as much as possible may lead the students to develop better trust in schools. Once there is campus crisis, it can reduce the possibility of students’ showing negative emotion and spreading rumors. According to the results, implications were provided as a reference for optimizing public health incident crisis emergency handling and enhancing students’ mental health.